Algebraic specifications and refinement for component-based development using RAISE - Estévez, Elsa Clara (2002)
There are two main activities in Component-Based Development: component development, where we build libraries for general use, and component integration, where we assemble an application from existing components. In this work, we analyze how to apply algebraic specifications with refinement to component development. So we restrict our research to the use of modules that are described as class expressions in a formal specification language, and we present several refinement steps for component development, introducing in each one design decisions and implementation details. This evolution starts from the initial specification of a component as an abstract module, and finishes with the final deployment as fully implemented code. The usage of formal tools helps to assure the correctness of each step, and provides the ground to introduce complementarytechniques, such as bisimulations, for the process of component integration.